PENGARUH KONSENTRASI LARUTAN ASAM ASETAT DAN LAMA PERENDAMAN TERHADAP SIFAT FISIK DAN KIMIA GELATIN KULIT BABI - Micron Rahmad Binambuni; Meity ., Sompie; Indyah ., Wahyuni (AGRI-SOSIOEKONOMI, 2018)
The objective of the study was to examine the extent to which the effect of different concentrations of acetic acid and the duration of immersion in acetic acid (CH3COOH) solution to the physicochemical gelatin of pigskin. This research has been carried out from September to December of 2017 at Animal Product Technology Laboratory of Faculty of Animal Husbandry of Sam Ratulangi University of Manado and the analysis was done at Food Engineering Laboratory, Faculty of Agricultural Technology Universitas Gadjah Mada Yogyakarta. This study used a 3x3 factorial pattern design with concentration treatment and long immersion in acetic acid (CH3COOH) solution, each treatment was repeated three times (Steel and Torrie, 2001). The results showed that the pigskin gelatin produced from 3% acetic acid solution and immersion time 24 hours had the best physicochemical properties.